Motorized walking stick / Muhammad Danial Abdul Aziz, Muhammad Aiman Abd Salleh and Muhammad Azharudin Che Mamat - Abdul Aziz, Muhammad Danial; Abd Salleh, Muhammad Aiman; Che Mamat, Muhammad Azharudin (2015)
The motorized walking stick is designed to help people with walking disabilities travel more quickly and while exerting energy. Today, the existing walking stick is used by the elderly and handicap with walking difficulty. Using the existing walking stick is somewhat troublesome because they need to use a lot -of energy lifting the walking stick forward. The existing walking stick is also of a significant weight which would be considered heavy for an older, weaker person to lift repeatedly. The motorized walking stick project is the solution which the elderly and handicap can use as a walking aid. The motorized walking stick is a project which is based on the existing 4 legged walking stick, also known as a reciprocal walker. It is then outfitted with a system which allows it to move by simply utilizing 3 buttons. The motorized walking stick also has a standing platform which allows the user to travel while standing on it.